Systematic and liquidity risk in subprime-mortgage backed securities - Mardi Dungey; Gerald P. Dwyer; Thomas Flavin (Federal Reserve Bank of Atlanta, 2011)
The misevaluation of risk in securitized financial products is central to understanding the financial crisis of 2007 - 8. This paper characterizes the evolution of factors affecting collateralized debt obligations based on subprime mortgages. A key feature of subprime-mortgage backed indices is that they are distinct in their vintage of issuance. Using a latent factor framework that incorporates this vintage effect, we show the increasing importance of a common factor on more senior tranches during the crisis. We examine this common factor and its relationship with spreads. We estimate the effects on the common factor of the financial crisis.
Keywords: G12; G01; C32; 330; asset-backed securities; subprime mortgages; financial crisis; factor models; Kalman filter; Asset-backed security; Subprime-Hypothek; Marktliquidität; Systemrisiko; Finanzmarktkrise; Zustandsraummodell; Schätzung; Welt